The well-argued cause - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Environments and livelihoods. Strategies for sustainability By K Neefjes, Development guidelines, Oxfam, 2000. 288 pp. ISBN 0 85598 440 6 GBP 11.50 Euro 18.60